Florida’s Harmful Algal Bloom (HAB) Problem: Escalating Risks to Human, Environmental and Economic Health With Climate Change - Heil, Cynthia Ann; Muni-Morgan, Amanda Lorraine (Frontiers in Ecology and Evolution, 2021)
Please see revised manuscript.